Implementasi Access Control List Pada Mikrotik dalam Mengamankan Koneksi Internet Koperasi Sumber Dana Mutiara - Bil Klinton Sihotang; Sumarno Sumarno; Bahrudi Efendi Damanik (JURIKOM (Jurnal Riset Komputer), 2020)
The need for information and internet access at this time is very high. To accept it is wrong only with computer networks as a medium. In a network that requires a network that has been segmented using a Virtual Local Area Network (VLAN), the application of an Access Control List (ACL) is required to be granted access rights for each device in the network. The Access Control List (ACL) can filter the data traffic of a network by controlling whether the packets are passed or issued. A network is built using several different network devices, one of which is a router. A router is a tool that can process different data packet networks (between networks) through a process called routing. lots of companies that produce routers, mikrotik is one of the companies that produce routers. mikrotik is easy to do because it uses Winbox in Gui's view, besides that the hotspot server in it is provided with several management facilities that can be arranged according to network requirements